Detection of Rickettsia spp. in ticks of wildlife fauna from Costa Rica: First report of Rickettsia rhipicephali in Central America - Rolando D. Moreira-Soto; Andres Moreira-Soto; Ólger Calderón-Arguedas; Mauricio Jiménez; Eugenia Corrales-Aguilar; Adriana Troyo (Ticks and Tick-Borne Diseases, 2023)
In the past two decades, new species of Rickettsia have been detected and described worldwide, some of them considered pathogenic for humans. Although Costa Rica is considered a biodiversity hotspot, the knowledge about rickettsiae in sylvatic ecosystems and wild animals is scarce. The aim of this preliminary study was to detect and identify species of Rickettsia in ticks collected from wild animals in Costa Rica. A total 119 ticks were collected from 16 animal host species belonging to diverse vertebrate families (Didelphidae, Procyonidae, Felidae, Choloepodidae, Bradypodidae, Myrmecophagidae, Tayassuidae, Tapiridae, Phyllostomidae, Bufonidae, Geoemydidae, Boidae, Colubridae), and they were grouped into 43 pools to detect the presence of Rickettsia spp. DNA by PCR targeting the gltA gene. In positive pools, amplicons of the ompA, sca5 (ompB), and/or htrA genes were also amplified to identify the species present. The identification of some ticks was also confirmed by molecular methods. Four species of Rickettsia were detected in eight (19%) tick pools: Rickettsia amblyommatis in four pools of Amblyomma geayi (host: Caluromys derbianus) and one pool of Amblyomma cf. parvum (host: Nasua narica), Rickettsia rhipicephali in one pool of Dermacentor latus (host: Tayassu pecari), ‘Candidatus Rickettsia colombianensi’ in one pool of Amblyomma sp. nymphs (host: Boa constrictor), and Rickettsia sp. genotype IbR/CRC in one pool of Ixodes cf. boliviensis (host: Puma concolor). This is the first molecular detection of R. rhipicephali in Central America, and of ‘Candidatus R. colombianensi’ in Costa Rica. Results show that diverse wild animals and their ticks are associated with several species of rickettsiae in Costa Rica, which may come in contact with humans and other domestic animals in sylvatic environments.